The Role of Women on Boards as A Mechanism to Improve Carbon Emission Disclosure and Firm Value - Monica, Monica; Daromes, Fransiskus Eduardus; Ng, Suwandi (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 16 No 2 (2021), 2021)
This study investigates the role of women on boards as a mechanism to improve carbon emission disclosure, as a mediating effect influence on firm value. The population includes 122 nonfinancial companies listed on the Indonesia Stock Exchange from 2015 to 2019. The results of path analysis reveal that women on boards have a positive and significant effect on carbon emission disclosure, a positive but insignificant effect on firm value, and that carbon emission disclosure is pivotal in mediating women on boards and firm value. This study provides insights that persuade companies to maintain relationships with stakeholders by implementing environmental awareness and disclosing sustainability reports. Carbon emission disclosure as part of the sustainability report is a form of good corporate action in maintaining the balance of living systems on earth. Keywords:  women on boards, carbon emissions disclosure, firm value